Green innovation effect of emission trading policy on pilot areas and neighboring areas: An analysis based on the spatial econometric model. (September 2021) - Du, Gang; Yu, Meng; Sun, Chuanwang; Han, Zhao
Abstract: This paper takes China's pilot emission trading policy as a quasi-natural experiment to study the green innovation effect. Based on the green patent data of listed companies in China from 2000 to 2018, the spatial Durbin model was used to explain the green innovation effect of the emission trading policy on pilot areas and neighboring areas at the national level, and the heterogeneity was further discussed according to the patent types in this paper. Further, the interaction effect of the policy and government intervention was studied in this paper. The conclusions can be obtained as follows: First, the emission trading policy has a significant promotion effect on the green innovation in the pilot areas, and a significant inhibitory effect in the neighboring areas. Second, there is a patent type heterogeneity between the green invention innovation effect and the green utility model innovation effect. The emission trading policy only shows a significant spatial spillover effect in green utility model innovation. Third, a high level of government intervention will inhibit the green innovation effect. This article provides empirical evidence and policy implementations to better promote the green innovation by implementing the emission trading policy more rationally. Highlights: We study the green innovation effect of CETS on pilot areas and surrounding areas. The spatial dependence is considered in conducting spatial econometric model. The CETS shows a spatial spillover effect in green utility model innovation. A high level of government intervention will inhibit the green innovation effect. Suggestions on how to promote green innovation with CETS are put forward.